The Significant Effect of Infrastructure Development on Logistics Performance Index - Bentar, Dewang Rangga; Permana, Enda; Okitasari, Hanissa (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to explore the correlation between infrastructure development and LPI. Research Design and Methodology: A systematic literature review and bibliometric analysis were employed in this study, with a total of 82 pieces of literature relevant to the topic under discussion. Network and DAG visualizations were also created, each designed to map research topics and illustrate the causal relationships between the two subjects. Findings and Discussion: The results of this study confirm a significant relationship between infrastructure and LPI, with trade sector acting as a mediating factor. The results also show that ports and roads are infrastructure that should not be overlooked. Good governance and government are essential. Implications: In practice, policymakers should not ignore the impact of infrastructure development, especially on ports and roads. The development of communication networks (both internal and external channels) is recommended to improve government governance in managing infrastructure.